(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Inquest is an inquiry or investigation into the cause of death in cases of unnatural deaths, or if there is any suspicion or foul play suspected by the law or investi gation agencies. On request of a Police or Magistrate, the forensic pathologist conducts the medico-legal post-mortem examination. Many a time, it leaves the doctor in a dilemma to determine the exact cause of death especially where the his tory from relatives, police and the facts observed in the autopsy do not match the dots with each other. In these cases, the forensic pathologist sends the viscera for chemical analysis to the FSL (Forensic Science laboratory), which helps the doctor to conclude conclusions. Still, the forensic expert should not stop here giving full recognition to the viscera report only, instead, he should have done the autopsy meticulously and given importance to other factors in the crime scene, keeping all the differentials in his open mind. This case report explores the accidental discov ery of organochlorine compounds in the viscera of a deceased patient who suffered a neurocardiogenic vasovagal shock. The Forensic Science Laboratory (FSL) detected these compounds during routine toxicological analysis. The findings were incongruous with the clinical diagnosis of vasovagal shock and prompted further investigation into the potential sources and health implications of these substances. This report underscores the necessity of comprehensive forensic investigation and the potential for environmental contaminants to complicate death investigations.